THE TRADITIONAL GARMENT DECORATION BY KOMI-PERMYAKS: YESTERDAY AND TODAY - Maltseva, N.A. (Perm Federal Research Centre Journal, 2016)
Some methods of the traditional garment decoration of Komi-Permyaks are considered. Based on the available publications about clothing and its decoration, as well as on the author’s own field data and museum collections, the author presents patterned weaving and patterned knitting as ways to decorate clothing which have existed in this nation since ancient times. The author also demonstrates embroidery and block printing as borrowed garment decoration methods at a later time, at the end of the ХVΙΙΙ-ХΙХ century. In this article for the first time, attention is drawn to appliqué as a decoration method of the Komi Permian national costume and also some considerable information about the work of modern needlewomen is provided, along with the way they use their ancestors’ traditions of garment decoration.